Implementasi Algoritma SAW (Simple Additive Weighting) Dalam Pengambilan Keputusan Pembelian Mesin Produksi Pada PT Ardhi Karya Teknik - Rusmawan, Uus (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2021)
Ardhi Karya Teknik is a company engaged in construction, painting, cooling engineering and information technology. This company has difficulty in making decisions to buy equipment, especially for goods with a high enough value, because the goods purchased must meet certain criteria and be able to help the company's operations effectively and efficiently. This research was conducted to overcome the above, the method chosen in this study was SAW (Simple Additive Weighting) with the general stages: first entering data, second determining the weighting of each assessment criterion, third determining the best value of each criterion. , fourth calculates the value of the normalization matrix, fifth Calculate the final value for each data input by multiplying the normalized matrix with the weight matrix. The selected data is the data with the largest final value. Another method used in making an application is Waterfall. The SAW method is quite effective in assisting in decision making to purchase company operational support equipment.